2014
DOI: 10.1002/ijc.28685
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of epidemiological factors by breast tumor subtypes in Korean women: A case-case study

Abstract: Breast cancer is heterogeneous in clinical behavior by subtypes; however, it is unclear how this heterogeneity is related to epidemiological factors. To evaluate the differences in epidemiological factors by breast tumor subtypes, we investigated the associations of epidemiological factors between tumor subtypes in Korean women. From the Seoul Breast Cancer Study, a total of 3,058 patients with breast cancer were included in the analyses. Tumor subtypes were classified based on hormone receptor (HR) and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
4
14
1
Order By: Relevance
“…Early menarche (before age 12 years) and late menopause (after age 55 years) are associated with increased risk of BC, likely due to a longer lifetime exposure to estrogen and progesterone (American Cancer Society, 2016). Several studies demonstrated a link between menopausal status and BC risk and was seen across participants from Thailand (Anothaisintawee et al, 2014), India (Chattopadhyay et al, 2014), Pakistan (Song et al, 2014a), and Korea (Park et al, 2013). As expected, the studies showed an increased BC risk in women who had a lower age of menarche (Bhadoria et al, 2013;Chung et al, 2013) and a later age of menopause (Bhadoria et al, 2013;Shamsi et al, 2013;.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 80%
See 1 more Smart Citation
“…Early menarche (before age 12 years) and late menopause (after age 55 years) are associated with increased risk of BC, likely due to a longer lifetime exposure to estrogen and progesterone (American Cancer Society, 2016). Several studies demonstrated a link between menopausal status and BC risk and was seen across participants from Thailand (Anothaisintawee et al, 2014), India (Chattopadhyay et al, 2014), Pakistan (Song et al, 2014a), and Korea (Park et al, 2013). As expected, the studies showed an increased BC risk in women who had a lower age of menarche (Bhadoria et al, 2013;Chung et al, 2013) and a later age of menopause (Bhadoria et al, 2013;Shamsi et al, 2013;.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 80%
“…A study conducted in Malaysia found that the majority of BC cases were hormone receptor-negative (Horne et al, 2015). Conversely in a Korean study, 69.5% of BCs were hormone receptor-positive (Song et al, 2014a) and 44.6% of BCs were estrogen receptor-positive in an Indian study (Singh et al, 2014). Among participants from Korea, when estrogen receptor-positive/progesterone receptor-positive tumors were compared to estrogen receptor-positive/progesterone receptor-negative tumors, women with the latter were 4 years older at diagnosis and more likely to be postmenopausal (Chung et al, 2013).…”
Section: Hormone Receptor Statusmentioning
confidence: 98%
“…This is a follow-up study that included eligible patients previously enrolled in the Seoul Breast Cancer Study (SEBCS), a multicenter-based case-control study on breast cancer described elsewhere[ 32 , 33 ]. The patients with histologically confirmed incident breast cancer at department of surgery of Seoul National University Hospital (SNUH) or ASAN Medical Center (AMC) were recruited and enrolled in the SEBCS between 2001 and 2007.…”
Section: Methodsmentioning
confidence: 99%
“…The duration of lifetime endogenous estrogen exposure was calculated by subtracting the age at menarche from the age at diagnosis for premenopausal women and from the age at menopause for postmenopausal women. The duration of endogenous estrogen exposure before FFTP was defined as the period between menarche and FFTP for parous women and the period between menarche and diagnosis or menopause for pre- and postmenopausal nulliparous women, respectively, as previously described[ 33 ]. The reference groups were defined as the first category of each variable and the greater proportion in each variable including age and BMI for the statistical stability.…”
Section: Methodsmentioning
confidence: 99%
“…The Seoul Breast Cancer Study (SEBCS) is a multicenter-based case-control study of female breast cancer in Seoul, Korea as previously reported[ 29 , 30 ]. This two-stage GWAS included a total of 3,226 incident breast cancer cases.…”
Section: Methodsmentioning
confidence: 99%